A bite by the emerald snake, Hapsidophrys smaragdinus Schlegel, 1837 (Colubridae, Colubrinae) causing atopic eczema with comments on the formal documentation of non-front-fanged snakebites. (15th October 2022) - Weinstein, Scott A.; Vidal, Nicolas; Miralles, Aurélien
Abstract: The mixed quality evidence about non-front-fanged snake bites has included unsupported speculation and presumption; the possible role of atopy and/or primary hypersensitivity have often been prematurely discounted. Described is a medically insignificant bite by a captive African emerald snake, Hapsidophrys smaragdinus Schlegel, 1837 (Colubridae, Colubrinae) that caused the development of moderate Type IV hypersensitivity; the 44-year-old male victim experienced persistent pruritis and an erythematous bite site maculopapular dermatitis that slowly resolved and required 6 days for full resolution. The victim had received several previous medically insignificant bites from non-front-fanged snakes. Brief comparison is made with a previously reported case consistent with a mixed clinical picture of local mild envenoming and hypersensitivity from a bite by another colubrine, the coin snake ( Hemmorhois nummifer ). This case highlights slowly accumulating evidence supporting the risk of acquired and primary hypersensitivity to some snakebites in susceptible individuals. In order to provide accurate medical risk profiles for less-known snake species it is essential that the case of any patient developing acute or delayed effects from bites by these species is formally documented. The need for further attention to atopic risks, especially in private collectors, is emphasised with consideration of venom/other ophidian product-induced anaphylaxis. Highlights: A bite by the non-front-fanged African emerald snake, Hapsidophrys smaragdinus (Colubridae) is described. Although initially unremarkable, during the next day a pruritic maculopapular dermatitis developed at the site of the bite. The risk of Type IV hypersensitivity and atopic dermatitis from non-front-fanged snakebites is considered.